A BiVO4 Photoanode with a VOx Layer Bearing Oxygen Vacancies Offers Improved Charge Transfer and Oxygen Evolution Kinetics in Photoelectrochemical Water Splitting. (31st January 2023) - Liu, Boyan; Wang, Xin; Zhang, Yingjuan; Xu, Liangcheng; Wang, Tingsheng; Xiao, Xiong; Wang, Songcan; Wang, Lianzhou; Huang, Wei
Abstract: Sluggish oxygen evolution kinetics are one of the key limitations of bismuth vanadate (BiVO4 ) photoanodes for efficient photoelectrochemical (PEC) water splitting. To address this issue, we report a vanadium oxide (VOx ) with enriched oxygen vacancies conformally grown on BiVO4 photoanodes by a simple photo‐assisted electrodeposition process. The optimized BiVO4 /VOx photoanode exhibits a photocurrent density of 6.29 mA cm −2 at 1.23 V versus the reversible hydrogen electrode under AM 1.5 G illumination, which is ca. 385 % as high as that of its pristine counterpart. A high charge‐transfer efficiency of 96 % is achieved and stable PEC water splitting is realized, with a photocurrent retention rate of 88.3 % upon 40 h of testing. The excellent PEC performance is attributed to the presence of oxygen vacancies in VOx that forms undercoordinated sites, which strengthen the adsorption of water molecules onto the active sites and promote charge transfer during the oxygen evolution reaction. This work demonstrates the potential of vanadium‐based catalysts for PEC water oxidation. Abstract : A vanadium oxide with enriched oxygen vacancies (VOx ) was developed as an efficient oxygen evolution cocatalyst for BiVO4 photoanodes. The optimized BiVO4 /VOx photoanode exhibits a high photocurrent density of 6.29 mA cm −2 at 1.23 V versus the reversible hydrogen electrode under AM 1.5 G illumination, and a high charge‐transfer efficiency of 96 % is attained. Stable PEC water splitting is achieved for 40 h.